1887 Dakota Terr. Laws 165-66, ch. 58, &sect - (:unkn) unknown (My University, 1887)
If any person shall kill or shoot any wild duck, goose or brant with any swivel gun, or any kind of gun except such as is commonly shot from the shoulder, or shall use medicated or poisoned food to capture or kill any of the birds named in this act, he shall be deemed guilty of a misdemeanor, and upon conviction shall be fined twenty-five dollars for each offense, and shall stand committed to the county jail for thirty days unless such fine and the costs of prosecution are sooner paid.
8
Keywords: HUNTING REGULATION